ЭСТЕТИКАЛЫҚ ТӘРБИЯ ЖЕКЕ АДАМНЫҢ ҚӘЛИПЛЕСИЎИНИҢ ТИЙКАРЫ - Уразимова, Т.В. (SCIENCE and SOCIETY, 2017)
The article is dedicated to modern contents of aesthetic, spiritual-creative formation of personality. In modern society attention increased to problem of the forming all-round developed, spiritually rich and creative personalities. The personality his spiritual and moral look are formed, first of all, in the process of education. That’s why the process of education is necessary to found on making the conditions for unbringing of the creative personality, ready to a dialogue, cooperation and creative activity in different spheres of life.
Keywords: pedagogics; social sphere; education process; methodology; methods of education; upbringing; creative work